MURNIATI AGUSTIAN - admin, Keguru (Penerbit STKIP PGRI Bangkalan, 2019)
Abstract This research aimed to examine whether there are differences in terms of effectivity in the learning experiences on thematic learning in fourth grade. The research was conducted at SD Regina Caeli, Bogor. The type of research is a quasi experiment with the nonequivalent control group design. Data was collected through administering pretest and posttest in experiment group 1 using learning experience of reading, listening, watching video and experiment group 2 using learning experience of discussion, presentation, and role playing. The collected data was analyzed through scoring, converting, determining average, determining frequency distribution, and comparising the mean. The hypothesis test was analyszed using independent t test. The result of the research showed that there was a significant difference of effectiveness. The result showed tcount = 2,219> ttable = 2,005 in which the post-test score in the two groups were compared. The result indicated H0 was rejected. The effectiveness as indicated by comparing the pre-test and post-test score in the experiment group 2 with learning experience of discussion, presentation, and role playing showed t-test scored 3,316 which was higher thanthe ttable 2,005. It indicated that H0 was rejected. It can also be seen that the improvement of learning experience through the learning outcomes in the control class was 18.53 point from the mean pretest 56.79 and the postest 75.32. While in the experimental class there is an increase 25.07 point from the mean pretest 56.07 and the posttest 81.14. It concludedthat there was diffrenece in terms of effectiveness in the learning experience in the thematic learning for fourth graders of Regina Caeli Elementary School, with the most effective learning experience found in the experimental group 2 through the experience of learning discussion, presentation and role play.